Immunization with a mucosal, post-fusion F/G protein-based polyanhydride nanovaccine protects neonatal calves against BRSV infection - Maina, Teresia W.; Grego, Elizabeth A.; Broderick, Scott; Sacco, Randy E.; Narasimhan, Balaji; McGill, Jodi L. (Frontiers in Immunology, 2023)
Human respiratory syncytial virus (HRSV) is a leading cause of death in young children and there are no FDA approved vaccines. Bovine RSV (BRSV) is antigenically similar to HRSV, and the neonatal calf model is useful for evaluation of HRSV vaccines. Here, we determined the efficacy of a polyanhydride-based nanovaccine encapsulating the BRSV post-fusion F and G glycoproteins and CpG, delivered prime-boost via heterologous (intranasal/subcutaneous) or homologous (intranasal/intranasal) immunization in the calf model. We compared the performance of the nanovaccine regimens to a modified-live BRSV vaccine, and to non-vaccinated calves. Calves receiving nanovaccine via either prime-boost regimen exhibited clinical and virological protection compared to non-vaccinated calves. The heterologous nanovaccine regimen induced both virus-specific cellular immunity and mucosal IgA, and induced similar clinical, virological and pathological protection as the commercial modified-live vaccine. Principal component analysis identified BRSV-specific humoral and cellular responses as important correlates of protection. The BRSV-F/G CpG nanovaccine is a promising candidate vaccine to reduce RSV disease burden in humans and animals.